2013
DOI: 10.1021/om401017t
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine-Substituted (η5-Pentadienyl) Manganese Carbonyl Complexes: Geometric Structures, Electronic Structures, and Energetic Properties of the Associative Substitution Mechanism, Including Isolation of the Slipped η3-Pentadienyl Associative Intermediate

Abstract: The molecule (η5-Me2Pdl)Mn(CO)3 (η5-Me2Pdl = 2,4-dimethyl-η5-pentadienyl) has been prepared by a new method and used as a starting material to prepare the molecules (η5-Me2Pdl)Mn(CO) n (PMe3)3–n (n = 2, 1) by phosphine substitution for carbonyls. The first carbonyl substitution is achieved thermally in refluxing cyclohexane, and the second carbonyl substitution requires photolysis. At room temperature in benzene the associative intermediate (η3-Me2Pdl)Mn(CO)3(PMe3) that precedes the initial loss of carbonyl i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 99 publications
1
5
0
Order By: Relevance
“…In the first reaction, translational entropy favors the product, and in the second reaction, translational entropy favors the reactants. The result that the same Gibbs energy change is obtained for both reactions indicates that solvation and the method we developed previously for the solution entropy are performing well for these complexes. There is little uncertainty that the dissociation energy is on the same scale as the axial/equatorial exchange energy, which as mentioned before is not observed up to 80 °C.…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations
“…In the first reaction, translational entropy favors the product, and in the second reaction, translational entropy favors the reactants. The result that the same Gibbs energy change is obtained for both reactions indicates that solvation and the method we developed previously for the solution entropy are performing well for these complexes. There is little uncertainty that the dissociation energy is on the same scale as the axial/equatorial exchange energy, which as mentioned before is not observed up to 80 °C.…”
Section: Resultssupporting
confidence: 63%
“…The following two dissociations were modeled in acetonitrile: [ ( μ ‐SMe ) 2 Fe 2 ( CO ) 6 ] 2 2 [ false( SMe false) Fe ( CO ) 3 ] [ ( μ ‐SMe ) 2 Fe 2 ( CO ) 6 ] 2 + 2 NCMe 2 [ false( SMe false) Fe ( CO ) 3 NCMe ] In both cases, dissociation is disfavored computationally by 120 kJ/mol. The largest uncertainty in modeling dissociative or associative reactions in solution is the handling of the solution translational and rotational entropy contributions to the Gibbs energy . In the first reaction, translational entropy favors the product, and in the second reaction, translational entropy favors the reactants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pentadienyl (Pdl) and heteropentadienyl ligands are an integral part of the organometallic toolbox, and many pentadienyl complexes have been synthesized since 1962 . One of the most prominent protagonists in this field is Ernst, who showed that pentadienyls can adopt not only several conformations, namely the W , S , and U conformations (Chart ), but also multiple coordination modes such as η 1 , η 3 , and η 5 . Nevertheless, most of these investigations have employed alkyl- and trimethylsilyl-substituted derivatives. ,,− …”
Section: Introductionmentioning
confidence: 99%